Determinant of criminal activities by some Nigerians residing in Malaysia: a socio-economic perspective - Adeyemi, Adewale Abideen; Amuda, Yusuf Jelili; Abdul Razak, Dzuljastri; Mohamed, Kamil Naail; Olaniyi, Oladokun Nafiu (2015)
Crimes pose a threat to any society. Considering its implication for the socio-economic activities and development of any country, the cost of crime is therefore burdensome not only to the government but also to the citizen. Controlling criminal activities is therefore imperative to prevent the many resulting negative consequences. Effective control of criminal activities unequivocally depends on proper understanding of crimes and the factors contributing to criminal behaviour. Given the rising number of reported Nigerian criminal activities in Malaysia, the need arises as to understand the underlying motives for such behaviour as part of any attempt to reduce such criminal activities. The current study therefore explores the factors contributing to the criminal behaviour of some Nigerians residing in Malaysia. In view of the prominence of socio-economic factors in explaining criminal behaviour, this study therefore explores this rising phenomena from a socio-economic perspective. Accordingly, this study seeks to identify the major socio-economic factors that contribute to high crime rates among some Nigerians living in Malaysia. In addressing this objective, this study employs the Analytical Hierarchy Process (AHP) whereby the socio-economic factors are ranked according to their contribution to the crime rate. It is expected that the findings of this study will shed light on the root causes of this menace thereby offering policy makers greater information and insights through which to better curb such criminal activities.